2023
DOI: 10.1001/jamainternmed.2022.5261
|View full text |Cite
|
Sign up to set email alerts
|

Use Trends and Recent Expenditures for Cervical Cancer Screening–Associated Services in Medicare Fee-for-Service Beneficiaries Older Than 65 Years

Abstract: ImportanceSince 1996, the US Preventive Services Task Force has recommended against cervical cancer screening in average-risk women 65 years or older with adequate prior screening. Little is known about the use of cervical cancer screening–associated services in this age group.ObjectiveTo examine annual use trends in cervical cancer screening–associated services, specifically cytology and human papillomavirus (HPV) tests, colposcopy, and cervical procedures (loop electrosurgical excision procedure, cone biopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Among the patients studied by Qin et al, 1 it is possible that the identified costs are going to extra testing among those who do not need it, while there may be limited or no testing among those who do require testing because of higher baseline risk.…”
Section: Related Article Page 11mentioning
confidence: 99%
See 3 more Smart Citations
“…Among the patients studied by Qin et al, 1 it is possible that the identified costs are going to extra testing among those who do not need it, while there may be limited or no testing among those who do require testing because of higher baseline risk.…”
Section: Related Article Page 11mentioning
confidence: 99%
“…5 However, management guidelines complicate these recommendations, as they recommend ongoing surveillance testing for all women with a history of HSIL for at least 20 to 25 years after the HSIL result because of an increased risk of cervical cancer and precancers. 5 Because the tests offered for surveillance (cytology, human papillomavirus [HPV], or the 2 tests combined) are the same as those provided for screening, knowing whether the testing is performed for screening or for surveillance is difficult; thus, understanding the appropriateness of the testing in women older than 65 years in Jin et al 1…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study examined the annual use trends of cervical cancer services in women covered under traditional Medicare plans over the course of 21 years as well as the estimated cost of these services in the year 2019 1 . Among the key findings were that more than 1.3 million women older than 65 years who were covered by Medicare fee‐for‐service programs received cervical cancer screening in 2019, and this incurred a cost of more than $83 million.…”
mentioning
confidence: 99%